2012
DOI: 10.1007/s11252-012-0234-7
|View full text |Cite
|
Sign up to set email alerts
|

Snake parasitism in an urban old-growth forest

Abstract: Urban-associated changes can have immediate or long-term consequences on animal populations. Such changes may be assessed through parasite prevalence and abundance in wildlife hosts, as urbanization can influence parasitism and disease transmission in wildlife. Snakes are widespread and diverse vertebrates that often persist in urban environments; however, parasitism of snakes in urban environments has yet to be studied, leaving the roles of snakes in parasite transmission uncharacterized. Field ecology, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In this region there are hundreds of rainforest fragments measuring 1 to 600 ha very close to urban areas. This combination of environments favors the parasitism of snakes by ticks (BENTES, 2013), which may be related to local parasitism dynamics (DAVIS et al, 2012). Despite this fact, only one earlier study has reported specimens of A. dissimile parasitizing a Boa constrictor captured in 1975 in an "INPA secondary forest" (ADIS, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…In this region there are hundreds of rainforest fragments measuring 1 to 600 ha very close to urban areas. This combination of environments favors the parasitism of snakes by ticks (BENTES, 2013), which may be related to local parasitism dynamics (DAVIS et al, 2012). Despite this fact, only one earlier study has reported specimens of A. dissimile parasitizing a Boa constrictor captured in 1975 in an "INPA secondary forest" (ADIS, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Both species can also host Hepatozoon eurytopis Telford (Telford 2010). Davis et al (2012) did not report Hepatozoon in these species, although only two individuals of each were sampled, while prevalence was 48% in Agkristrodon contortrix. (L.) (Copperhead Snake; n = 25), all from urban woodland in Tennessee.…”
Section: Discussionmentioning
confidence: 94%
“…Concurrently, we also checked for ectoparasites (ticks or mites), which were rarely observed (<7% of snakes). Thus, hemoparasites were used as a proxy for parasite burden because hemoparasites are common in snakes (Davis et al, 2012; Telford, 2009), can influence fitness‐related traits in snakes (Madsen, Ujvari, & Olsson, 2005; but see Brown, Shilton, & Shine, 2006), and can be determined in a minimally invasive fashion (i.e., via blood smears: see Section 2.3 below). We subcutaneously implanted each snake with a passive integrated transponder (12 mm) for future identification and returned each snake to its site of capture within 18 hr.…”
Section: Methodsmentioning
confidence: 99%